2022
DOI: 10.1021/acsomega.1c07345
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Waste Plastic Bottle-Based Pyrolysis Oil as an Alternative Fuel

Abstract: In the present work, an experimental investigation is carried out on the use of waste plastic oil produced from waste poly(ethylene terephthalate) (PET) bottles (WPOB) as an alternative fuel for diesel engines. The physical and chemical properties of WPOB were analyzed, and it was found that it has fuel properties similar to those of petroleum fuels. The WPOB was tested in a diesel engine to evaluate the effect of WPOB on combustion and emissions characteristics. In addition, particulate matter (PM) emissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…According with experiment results, BSFC decreased for all test fuels as engine load increased. This is because the increment in brake power is higher than that of the increase in fuel consumption [7]. Due to their lower energy content as compared to diesel fuel, the COME and PLOME are shown with higher BSFC than diesel fuel [8].…”
Section: Analysis Of Engine Performancementioning
confidence: 96%
“…According with experiment results, BSFC decreased for all test fuels as engine load increased. This is because the increment in brake power is higher than that of the increase in fuel consumption [7]. Due to their lower energy content as compared to diesel fuel, the COME and PLOME are shown with higher BSFC than diesel fuel [8].…”
Section: Analysis Of Engine Performancementioning
confidence: 96%
“…PET combustion results in higher carbon-based emissions. Therefore, in diesel engine testing, liquid fuel from PET pyrolysis will be mixed with diesel fuel, with a maximum of 20% of pyrolysis liquid fuel by volume, to maintain combustion characteristics and emissions similar to diesel fuel [40] IOP Publishing doi:10.1088/1755-1315/1201/1/012011 6 Although most studies only use one type of plastic in their pyrolysis, this is difficult to apply in practical use due to the mixed nature of everyday waste. Matuszewska et al (2022) reported that pyrolysis with mixed plastic feed resulted in 75-87% yield of bio-oil, while the remaining 13-25% comprised gas and char [41].…”
Section: Pyrolysis Technology For Plastic Wastementioning
confidence: 99%
“…3 To combat plastic pollution and its climate impact, it is essential to explore alternative ways of utilizing plastic waste. [4][5][6] The world's current energy demand is increasing, which has led to increased environmental pollution from using fossil fuels for electricity production. However, reusing plastic waste for energy generation offers a solution to both electricity generation and environmental pollution reduction.…”
Section: Introductionmentioning
confidence: 99%